UAV assisted cooperative caching on network edge using multi agent Actor critic reinforcement learning - Araf, Sadman; Saha, Adittya Soukarjya; Eunus, Salman Ibne (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.